Bactericidal effect of graphene oxide and reduced graphene oxide: Influence of shape of bacteria - Sengupta, Iman; Bhattacharya, Proma; Talukdar, Monikangkana; Neogi, Sudarsan; Pal, Surjya K.; Chakraborty, Sudipto (Colloid and interface science communications, 2019)
The emergence of multi-drug resistant bacteria due to the misuse of antibiotics and inadequate development of antibiotic drugs is a global threat to human health. Recent development in materials research caused the emergence of nanomaterials with promising bactericidal properties. Carbon based nanomaterials like graphene and graphene oxide(GO) have appealed researchers for antimicrobial properties, although some researchers claimed that they promote bacteria growth. To address the conflict, authors performed experiments to study the influence of GO and reduced GO(rGO) on gram positive Staphylococcus aureus and gram negative Pseudomonas aeruginosa bacteria. GO restricts S. aureus and P. aeruginosa cell growth by 93.7% and 48.6% whereas, percentage inhibition by rGO are 67.7% and 93.3% respectively. GO destructs bacteria by cell membrane damage through chemical reaction whereas, rGO induce mechanical stress and pierce the cell membrane. Shape and type of bacteria act as the controlling factors in determining the bactericidal efficacy of the nanomaterials. [Display omitted] •GO and rGO nanosheets impede bacterial growth significantly.•Bactericidal efficacy of GO and rGO are influenced by shape and type of bacteria.•GO damages bacteria cell membrane by reaction driven interaction with the functionalities.•Bactericidal efficacy of rGO is dependent upon application of mechanical stress and generation of ROS.